Formation of a strategy for countering and identifying AI technologies in the fight against disinformation under martial law - Cherep, Oleksandr; Kaliuzhna, Yuliia; Mykhailichenko, Lubomir; Markova, Svitlana; Naumenko, Yevhen (Technology audit and production reserves, 2025)
The methodological basis of the study is a set of techniques, principles, general theoretical, special, interdisciplinary methods of scientific research. To achieve the set goal, the dialectical method of scientific knowledge was used – to study disinformation in martial law and determine the role of artificial intelligence (AI) in its detection and neutralization. The use of a systemic approach made it possible to determine the features of the spread of disinformation through social networks, traditional media and automated bot farms, for the manipulation of public opinion. The operations research method was used to determine the advantages and disadvantages of AI tools aimed at detecting disinformation. Methods of analogies and comparison – to determine modern methods of combating fake news, including machine learning algorithms, natural language processing and image analysis. It was established that the main problem for increasing the effectiveness of combating disinformation is the implementation of European experience in using AI. The use of systemic and critical analysis allowed to explore the international experience of using AI tools in the field of information security, their effectiveness in detecting deepfakes and other forms of false content. A comprehensive strategy for countering disinformation in Ukraine is proposed. The proposed strategy, unlike the existing strategy, takes into account the use of artificial intelligence technologies to identify fake content in social networks and news channels, the formation of a special body to analyze digital content and the development of a digital society. The comprehensive strategy, unlike the existing ones, includes the expanded use of AI to monitor the information space, combining automated analysis with human control; the implementation of state initiatives to regulate fake content and increase the level of media literacy of the population. The research results will be useful for scientists, information security experts, journalists and state bodies involved in combating disinformation. The proposed approaches will contribute to strengthening the information protection of Ukraine and reducing the impact of fake news on society.